2009
DOI: 10.1186/1423-0127-16-59
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of localization and interactions of apoptotic proteins

Abstract: During apoptosis several mitochondrial proteins are released. Some of them participate in caspaseindependent nuclear DNA degradation, especially apoptosis-inducing factor (AIF) and endonuclease G (endoG). Another interesting protein, which was expected to act similarly as AIF due to the high sequence homology with AIF is AIF-homologous mitochondrion-associated inducer of death (AMID). We studied the structure, cellular localization, and interactions of several proteins in silico and also in cells using fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…The role of AMID in apoptosis is also unclear. By in silico methods and image analysis, the localization of AMID was predicted to be cytoplasmic, most probably incorporated into the cytoplasmic side of the cellular membranes (52,53). It was also suggested that AMID in human leukemia Jurkat T-cells after apoptosis induction is associated with the plasma membrane by immunohistochemical study (54).…”
Section: Discussionmentioning
confidence: 99%
“…The role of AMID in apoptosis is also unclear. By in silico methods and image analysis, the localization of AMID was predicted to be cytoplasmic, most probably incorporated into the cytoplasmic side of the cellular membranes (52,53). It was also suggested that AMID in human leukemia Jurkat T-cells after apoptosis induction is associated with the plasma membrane by immunohistochemical study (54).…”
Section: Discussionmentioning
confidence: 99%
“…Endo G, is a conserved nuclease, normally localized in the mitochondria [69]. Its N-terminus contains a mitochondrial localization sequence (MLS), which is cleaved upon successful transport of the Endo G precursor polypeptide across the outer mitochondrial membrane [70]. From the mitochondria, Endo G translocates in the nucleus and produces DNA degradation independent of caspases [71,72].…”
Section: Overview Of Caspase-independent Apoptosismentioning
confidence: 99%
“…). The global energy of each complexes was considered to be related to free binding energy and its higher negative value indicates higher free binding energy and thus higher interaction probability . Based on ensemble docking analysis, it is worth noting that the predicted pharmacological activity of curcumin against H. pylori infection targeting remarkable Cag oncoprotein is encouragingly similar to conventional drugs.…”
Section: Resultsmentioning
confidence: 99%